Zmiany struktur podmiotów świadczących usługi gastronomiczne w stołówkach szkolnych woj. dolnośląskiego w kontekście obowiązku wprowadzenia systemu HACCP - Kowalska, Anna (Changes of Structures of Gastronomic Services Subjects in School Canteens in Lower Silesia Voivodship in the Context of the Duty of Introduction of the HACCP System, 2005)
The access of Poland to the European Union imposed the obligation the enforce the HACCP system on producers and distributors of food products (who employ up to 50 people). Only few school canteens in Lower Silesia voivodship have enforced or are enforcing the HACCP system.School headmasters more and more often decide to lease canteens to private or catering firms. The main reason of this, is the lack of funds to modernize the canteens according to the HACCP system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 484-489